PERBANDINGAN KAJIAN SEMANTIK RUMPUN BAHASA MELAYU - Romi Firmansyah; Ricky Surya Aprian; Raden Mekar Ismayani (IKIP Siliwangi, 2018)
Semantic is a branch of linguistics that examines the meaning of words. The analysis of semantic is relates to the language and culture of people who use it. Occasionally, a same word has a different meaning or has an opposite meaning in the way it is use. For the example the Malay language which is the origin of Indonesian language. Apart from Indonesia, there are other countries that use Malay language which is called as Austronesia language. The countries that include to the Austronesia sociaty are Indonesia and Malaysia. This research examines the comparison meaning of Indonesian vocabulary with Malaysia using descriptive method. From the data collected, there are at least fiften world that have same pronunciation but have defferent meaning in their use. The objective of this study is how the Austronesia society are not wrong in interpreting and using it.